Video Projection-Mapping on Box Structures: Techniques and Applications for Immersive Storytelling - Matahari, Tombak (Faculty of Engineering and Technology, Sampoerna University, 2025)
This paper explores techniques and applications of video projection mapping on box structures to enhance immersive storytelling within an exhibition context. The study tries to find the best technical decisions for projector positioning, shadow minimization, and surface calibration through a practice-based approach. Equally important, the research focuses on visual communication strategies, including narrative development, visual style exploration, and typography optimization to ensure content readability. Using showcasing the development of the New Indonesia Nusantara Presidential Palace as a case study, this project combines scriptwriting, motion graphics, and a well-crafted two-minute storytelling sequence to engage the audience and effectively communicate architectural and developmental narratives. The findings show that the box structure, when combined with audio and well-executed motion graphics, can bring a new experience for exhibition and also serves as a new portable medium for projection mapping.